RhoA regulation in space and time. Issue 6 (29th January 2023) - de Seze, Jean; Gatin, Joséphine; Coppey, Mathieu
Abstract : RhoGTPases are well known for being controllers of cell cytoskeleton and share common features in the way they act and are controlled. These include their switch from GDP to GTP states, their regulations by different guanine exchange factors (GEFs), GTPase‐activating proteins and guanosine dissociation inhibitors (GDIs), and their similar structure of active sites/membrane anchors. These very similar features often lead to the common consideration that the differences in their biological effects mainly arise from the different types of regulators and specific effectors associated with each GTPase. Focusing on data obtained through biosensors, live cell microscopy and recent optogenetic approaches, we highlight in this review that the regulation of RhoA appears to depart from Cdc42 and Rac1 modes of regulation through its enhanced lability at the plasma membrane. RhoA presents a high dynamic turnover at the membrane that is regulated not only by GDIs but also by GEFs, effectors and a possible soluble conformational state. This peculiarity of RhoA regulation may be important for the specificities of its functions, such as the existence of activity waves or its putative dual role in the initiation of protrusions and contractions. Abstract : RhoA is a key regulator of cell cytoskeleton dynamics, usually described as a simple switch residing at the plasma membrane. In this review, we show that the highly diverse patterns of RhoA activity call for additional layers of regulation: RhoA residence time at the plasma membrane, localization in space and time, and positive/negative feedback loops.